Abolition of Exequatur in Brussels Ia Regulation – New Challenges for the National Judge (Croatia) - Poretti, Paula (LeXonomica, 2017)
This article will analyse and evaluate if and to what extent enforcement of judgments according to the Brussels Ia Regulation may be challenging for Croatian judges. It seeks to answer the questions a) which novelties in terms of recognition and enforcement of foreign judgments are introduced through the system of cross-border enforcement of judgments under Brussels Ia and b) with regard to the lack of implementation provisions in Croatian legal system, how will a new “adaptation device” according to Art. 54 of the Brussels operate. In particular, how and by whom will the adaptation of measure or order be carried out and how will it be challenged pursuant to Art. 54 (2) of the Brussels Ia Regulation. In a search for possible answers, approaches as well as solutions adopted in the legal systems of some Member States will also be taken into account. Considerations which can be attributed to the lack of provisions regarding implementation of the Brussels Ia Regulation in Croatian legal system will be highlighted.